#### Answer

$x^2-9$

#### Work Step by Step

$x+3=x+3$, $x^2-9=(x+3)(x-3)$, so the GCF is $x+3$ and the terms that are "not common" are $x-3$ so LCD$=(x+3)(x-3)=x^2-9$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$x^2-9$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.